Color Tuning of Luminescent Cationic Platinum(II) Complexes: Effects of Molecular Structures and Counter‐Anions. Issue 9 (25th June 2022) - Chaaban, Maya; Lee, Sujin; Vellore Winfred, J.S. Raaj; Lin, Xinsong; Ma, Biwu
Abstract : The photophysical properties of square planar Pt(II) complexes are often strongly dependent on their self‐assembly modes and intermolecular Pt⋯Pt interactions. Controlling these interactions is important to achieve valuable properties for various applications, such as light‐emitting diodes and environmental sensing devices. Herein, a series of highly luminescent ionic Pt(II) complexes with tunable emission colors are reported, by controlling the molecular structures and interactions in solid state. Four ionic Pt(II) complexes, with a general formula [Pt(C ^ N)(N ^ N)] + X − (C ^ N = 2‐phenylpyridine or 2‐(2, 4‐difluorophenyl)pyridine; N ^ N = 2, 2′‐bipyridine; X − = chloride (Cl − ) or tetraphenylborate (BPh4 − ), are designed, synthesized, and characterized. Due to the presence of intermolecular Pt⋯Pt interactions, strong metal–metal‐to‐ligand charge transfer (MMLCT) emissions are recorded in all four complexes with color changing from green to deep red in solid state. A high photoluminescence quantum efficiency (PLQE) of 81% is achieved for one of the complexes containing large BPh4 − anions, due to the site isolation effects. Detailed structural and photophysical characterizations reveal a clear correlation between the stacking of these Pt(II) complexes and their photophysical properties, which can be well regulated by the molecular structures and counter‐anions. Abstract : Emission color tuning of a series of cationic Pt(II) complexes from green to deep red has been achieved by changing the cyclometallating ligand and counter‐anion. A clear correlation between the photophysical properties of these compounds and their molecular packings is established.